A new genus of oak gallwasp, Protobalandricus Melika, Nicholls & Stone (Hymenoptera: Cynipidae: Cynipini) from California - Nicholls, James A.; Stone, Graham N.; Melika, George (Zootaxa, 2018)
We describe a new genus of cynipid oak gallwasp, Protobalandricus Melika, Nicholls & Stone (Hymenoptera: Cynipidae: Cynipini). Protobalandricus gen. nov. includes one previously described species, Disholcaspis spectabilis (Kinsey), which induces stem swelling-like galls on golden cup oaks, Quercus section Protobalanus. Descriptions of the genus and diagnostic characters, including DNA sequence data, are presented.